Discovery of glycerol phosphate and an immunogenic glycan motif in rhamnose-rich polysaccharides of Streptococcus uberis - Yao Shi; Göran Widmalm; Natalia Korotkova; Adrian Molenaar; Mark A. Holmes; Scott McDougall; Jetta J. E. Bijlsma; Nina M. van Sorge; Lindert Benedictus (Veterinary Research)
Abstract Streptococcus uberis is a causative pathogen of bovine mastitis with high genetic diversity. Rhamnose-rich polysaccharides (RPS) are abundant surface structures covalently anchored to peptidoglycan and represent promising vaccine candidates for several streptococcal pathogens. It was previously reported that the RPS of S. uberis strain 233 is composed of a repeating → 2)-α-l-Rhap-(1 → 3)-α-l-Rhap-(1 → disaccharide backbone decorated with α-d-Glcp side-chains. In this study, we identified a hitherto unknown glycerol phosphate (GroP) modification at the 6-OH of the Glc residue in S. uberis 233 RPS using nuclear magnetic resonance analysis. Comparative genomic analysis of 592 S. uberis genomes revealed significant diversity in the RPS biosynthesis gene cluster with six major RPS genotypes. RPS genotypes 1–4, representing 97.5% of the analyzed strains, all contained the rhamnan backbone biosynthesis genes shared between several streptococcal species, as well as a putative GroP transferase gene. Using rhamnan-reactive immune serum, we further demonstrated that rhamnan is a conserved and accessible glycan motif in S. uberis RPS genotype 1 and 2 strains, but this motif is inferred to be shielded by side-chains in genotype 4 strains. Importantly, experiments with sera from cattle, challenged intramammarily with S. uberis, revealed that the rhamnan backbone of S. uberis RPS is an immunogenic glycan motif and remained accessible to bovine IgG antibodies in the presence of single residue RPS side-chains. Overall, this study suggests that S. uberis RPS are modified with GroP and reports that RPS in most strains contain a conserved, immunogenic and antibody accessible rhamnan glycan motif.